PEMASARAN ONLINE ANEKA OLAHAN MAKANAN DI DESA JENDI, SELOGIRI, WONOGIRI - Irsyadul Ibad; Susilaningsih Susilaningsih (Universitas Sebelas Maret, 2019)
One of the challenges of developing SME products in Jendi is the difficulty in selling their products. Most SME entrepreneurs only sell their products directly around their place even though the development of internet technology and social media has created great opportunities for SME product marketing. These technological developments increase SMEs to be able to market their products with a wider network with minimal costs. However, there are still many who support SMEs that do not yet know how to market online through the internet and social media. Previous results of research on social media turned out to provide information about community consumption. The method used is through increasing the capacity of human resources in managing websites and social media. The stages of this service activity are as follows: Analysis of needs in program planning, Development of internal capacity Activities Increased knowledge of marketing management, Increased knowledge and technical skills in managing websites and social media, Increased soft skills improve website content and social media. The third is the development of a marketing network with relevant stakeholders. The results agreed upon in this activity were among others the initial coordination of activities, in-class training and camera providers as marketing support tools.Keywords: SMEs, Marketing, Online, Internet, Social Media